Genetic Studies in Some Oil Palm Breeding Populations in Malaysia - Ahiekpor, Emmanuel Kwaku Seke (1981)
Five oil palm breeding populations were studied for heritability, phenotypic correlations, path coefficient analysis and yield performances involving oil yield, number of bunches, single bunch weight, percentage fruit-to-bunch, percentage mesocarpto- fruit and percent age oil-to-wet me socarp. The breeding populations consisted of different families of Deli Duras, Teneras and Pisiferas grown at Banting between 1968 and 1970. Two methods, namely, parent offspring regression and combined (genotype x year) analyses were used to estimate heritabilities. Heritabilities using combined analysis were larger than those estimated using parent offspring regression. However, both methods showed that heritabilities for total bunch weight were lower than those of its component characters. The correlation studies for oil yield and its components showed wide variation in association in both magnitude and direction. Nevertheless, number of bunches and single bunch weight negatively and significantly correlated in four of the five populations studied.